Water use for bean crop in different growth stages - dos Santos, Renato Zorzenon; André, Romisio Geraldo Bouhid (Pesquisa Agropecuaria Brasileira, 1992)
The objective of this work was to analyse the water use efficiency for a bean crop (Phaseolus vulgaris, L.), cultivar Aroana-80, in different growth stages. A field experiment was conducted on the experimental area of ESALQ/USP. All the parameters for water balance determinations and physiological measures were taken in the center of the plot. The water balance approach associated with the physiological measurements showed to be important tools for analysing the different crop growth stages. The crop coefficient (Kc) showed to be proportional to the leaf area index during all crop growth stages.